Tecnologias digitais em cursos livres de inglês : lógicas da educação neoliberal - Barros, Emanuelle Silveira Nunes (2022)
The dynamics imbricated in society by passing through increasingly markedly neoliberal discourses in the most varied criteria beyond the economic. When dealing with the educational sector, we can identify marketing pillars, for example, in the characterization of English language learning as an investment linked to the ideal of socioeconomic prestige. In parallel to regulate this language, the formation of a wave of subjectivation of specific interest groups reverberates hegemonic narratives rooted on the coordination of English learning in English courses based on methodology often associated with the use of digital technologies. This dissertation, in this line of Technologies, Languages and Education, identifies the role of digital technologies in the pedagogical proposal of English, analyzing the uses of these resources and the practical impacts on free public education. As objectives, it is intended to point out the proposals for the pedagogical use of technologies; to understand the meanings of success in learning that cross the discourses of the investigated courses; and, punctuate the neoliberal values for education. Methodologically, it is characterized as a case study (YIN, 2015), under a qualitative approach, since it intends to evaluate the context based on the participants' experiences and related theory. Data were collected through semi-structured interviews based on Freeman's Faculty Research and Auerbach and Silverstein's (2003) coding process.